Vector characteristics of the sound field based on a single vector hydrophone - Chao Wang; Shuyang Jia; Yanhou Zhang; Qi Zhang; Rongxin Zhu (PLoS ONE, 2026)
The acoustic field in the ocean is a vector field, and its vector characteristics can be gained by a single vector hydrophone. This paper focuses on the vector characteristics of the sonic field, analyzes the coherence function, energy component proportion, and phase spectrum of the received signal from a single vector hydrophone. The purpose of the study is to establish a research foundation for applying the vector characteristics of sound field to target detection and recognition. The simulation results demonstrate that the total coherence function of the sound field is approximately 0.5 when the signal-to-noise ratio is −10 dB. At this point, the coherence spectrum of the sound field is approximately equivalent to the diffusion spectrum, and the target quadrant can be identified based on the phase difference of the sound field. The results of the anechoic pool and sea testing indicate that under the background noise condition, the coherence function values are generally below 0.2, except for some specific frequency points. Using coherence spectrum for detection can improve the SNR by about 8 dB. The overall coherence function of the sound field, the total sonic field spectrum and the coherence spectrum show evident interference of moving targets.